Creating an Uncontested Market Space and Making the Competition Irrelevant for Monumental Games Ltd. UK - Rafik, Javed (2007)
This project is an extension of the group project, titled 'Massively Multiplayer Online Games Industry: A Review and Comparison', undertaken by Javed Rafiq, Almuntaser Alhindawi and Sim Boon Seong from the MBA department of Nottingham University Business School.